2002
DOI: 10.1080/00984100290071054
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress in the Tissues of Rats After Chronic Exposure to Tcdd, 2,3,4,7,8-Pentachlorodibenzofuran, and 3,3',4,4',5-Pentachlorobiphenyl

Abstract: The abilities of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), 2,3,4,7,8-pentachlorodibenzofuran (PeCDF), 3,3',4,4',5-pentachlorobiphenyl (PCB126), and mixtures of these xenobiotics (toxic equivalents, TEQs) to induce oxidative stress in hepatic and brain tissues of rats have been investigated after chronic (30 wk) exposure to these congeners. TCDD, PeCDF, PCB126, and TEQs were administered daily to groups of rats at doses that corresponded to their toxic equivalency factors (TEFs), and the biomarkers of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 47 publications
8
29
0
Order By: Relevance
“…It was demonstrated that PCB77 can uncouple the catalytic cycle of CYP1A1, allowing heme iron within the active site of this enzyme complex to act as a Fenton catalyst and generating hydroxyl radicals from hydrogen peroxide (Schlezinger et al, 1999;Schlezinger et al, 2006). Other coplanar PCBs, such as PCB126 and PCB169 also markedly increased cellular oxidative stress in vascular endothelial cells, brain, and hepatic tissues (Twaroski et al, 2001;Hassoun et al, 2002;Ramadass et al, 2003) with superoxide anions being a major reactive oxygen species. Thus, induction of CYP1A1 or CYP1A2 may lead to generation of excess levels of reactive oxygen species, resulting in cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that PCB77 can uncouple the catalytic cycle of CYP1A1, allowing heme iron within the active site of this enzyme complex to act as a Fenton catalyst and generating hydroxyl radicals from hydrogen peroxide (Schlezinger et al, 1999;Schlezinger et al, 2006). Other coplanar PCBs, such as PCB126 and PCB169 also markedly increased cellular oxidative stress in vascular endothelial cells, brain, and hepatic tissues (Twaroski et al, 2001;Hassoun et al, 2002;Ramadass et al, 2003) with superoxide anions being a major reactive oxygen species. Thus, induction of CYP1A1 or CYP1A2 may lead to generation of excess levels of reactive oxygen species, resulting in cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that TCDD produces oxidative stress (55)(56)(57)(58). Low dose TCDD causes a sustained oxidative stress in liver that is dependent on the AHR but independent of the presence of CYP1A1 or CYP1A2 (49, 59, 60).…”
Section: Maternal Cyp1a2 Protects the Fetus From Tcdd-induced Mitochomentioning
confidence: 99%
“…Wasting (cachexia), thymic involution, tumor promotion, hepatotoxicity, developmental toxicity, and immunosuppression are a few of the pathological effects of TCDD (14,15). TCDD is also known to induce oxidative stress, production of superoxide and peroxide radicals, and DNA singlestrand breaks (16)(17)(18). However, the cellular and molecular mechanisms of TCDD-mediated pathologies are poorly understood.…”
mentioning
confidence: 99%
“…TCDD and related dioxins are well established ligands for aryl hydrocarbon receptor (AhR), which modulates transcriptional activation of many genes, including those involved in fatty acid metabolism (18), cell cycle regulation, immune response, and xenobiotic metabolism. Binding of TCDD to AhR triggers AhR nuclear translocation and its heterodimerization with AhR nuclear translocator (Arnt).…”
mentioning
confidence: 99%